Knowledge, attitudes, and adherence relating to COVID-19 and its prevention measures in high-risk districts of Uganda in 2020 - Methodius, Tubihemukama; Musewa, Angella; Mirembe, Bernadette Basuta; Birungi, Doreen; Nitumusiima, Sarah; Naigaga, Irene; Kabasa, John David; Bazeyo, William (Frontiers in Epidemiology, 2023)
Introduction COVID-19 is an infectious disease caused by severe acute respiratory syndrome coronavirus 2. There were no licensed vaccines or explicit medicines available for treatment at the time of conducting this study. Public health and social measures (PHSM) have been widely adopted to reduce the transmission of COVID-19. Hence, assessing people's knowledge, attitudes, and adherence/practices related to the management of COVID-19 is crucial for identifying the factors that may promote or hinder adherence to the implementation of PHSM. Methods We conducted a cross-sectional study in the Amuru, Kyotera, Wakiso, and Kampala districts of Uganda. We used a simple random sampling technique to select households and conducted face-to-face interviews in selected households. We administered questionnaires to respondents to assess the factors that promote or hinder adherence to and knowledge about PHSM implementation. We used a Likert scale to assess respondents’ attitudes toward COVID-19. Results Out of the 270 respondents, 54 (20%), 73 (27%), 42 (15.6%), and 101 (37.4%) were from the Kampala, Amuru, Wakiso, and Kyotera districts, respectively. Most of the respondents had adequate knowledge (72.2%), a high level of adherence (63.7%), and approximately 57.8% had good attitudes relating to COVID-19 and its prevention measures. An inferential analysis revealed that people from the Kampala district had higher chances (odds ratio = 4.668) of having a high level of knowledge compared to people from the Amuru district. It was also found that respondents who had a high level of (adequate) knowledge were twice as likely to have good attitudes compared to those with a low level of knowledge. In addition, people with good attitudes were 2.5 times as likely to adhere to the COVID-19 prevention measures compared to those with poor attitudes. Conclusion Most respondents had limited knowledge though the majority of them had adopted practices to prevent the spread of COVID-19. Respondents with low knowledge of COVID-19 need to be targeted, to improve their attitude toward the disease and their adherence to safe prevention practices.